Analisis Potensi Perekonomian Pedagang Kaki-Lima di Kota Langsa - Budiman, Iskandar (Jurnal Samudra Ekonomi dan Bisnis, 2021)
This article is based on the results of research, focused on the activities of hawker traders along Cut Nyak Dhien Street, Langsa City. There are more than seventy street vendors with various types of merchandise. The research aims to determine the role of the informal sector street vendors of economically weak groups in obtaining employment, the prospect of developing a culinary tourism business on family economic growth, and additional sources of local revenue. Data obtained through observation, interviews and documentation, and then processed using descriptive analysis techniques. The analysis results showed that street vendors in urban areas are a popular alternative to work. This condition is in synergy with the government program that arranges this area as a center for culinary tourism and is very helpful for traders to increase family income, as well as having an impact on increasing visitors and increasing local income.